Measuring Economic Value Added (EVA), Synergy Value, & MSMEs Upgrade Post-Acquisition: A Case Study of Ultra-Micro Holding in Indonesia - Bayu Hidayat; Eko Rizkianto (Universitas Negeri Semarang, 2023)
The Indonesian government assesses the urgency of the presence of a formal financial institution through the establishment of an ultra-micro holding. The formation of a holding is expected to be able to provide positive synergy and added value, which will have an impact on increasing the welfare of shareholders. The purpose of this research is to reveal the creation of corporate value through economic value added, value synergy, and MSMEs upgrade after the formation of ultra-micro holdings.The research data comes from the financial reports for the last 2 years before the formation and the last 1 year after the formation of ultra-micro holding. EVA is calculated using items that determine operational and capital costs. Calculation of synergy value using the discounted cash flow (DCF) model.The results obtained are that EVA is positive and higher than before the establishment of the ultra-micro holding, which shows management's ability to create an increase in the value of the company's assets. The resulting positive synergy reflects a successful holding process. The findings may help the company management and investors to analyze value creation and calculate the value synergies of the ultra-micro holding ecosystem.